Retinoid and carotenoid status in serum and liver among patients at high-risk for liver cancer. Issue 1 (December 2016) - Kataria, Yachana; Deaton, Ryan; Enk, Erika; Jin, Ming; Petrauskaite, Milita; Dong, Linlin; Goldenberg, Joseph; Cotler, Scott; Jensen, Donald; van Breemen, Richard; Gann, Peter
Abstract Background Approximately 2.7 million Americans are chronically infected with hepatitis C virus (HCV). HCV patients with cirrhosis form the largest group of persons at high risk for hepatocellular carcinoma (HCC). Increased oxidative stress is regarded as a major mechanism of HCV-related liver disease progression. Deficiencies in retinoid and carotenoid antioxidants may represent a major modifiable risk factor for disease progression. This study aims to identify key predictors of serum antioxidant levels in patients with HCV, to examine the relationship between retinoid/carotenoid concentrations in serum and hepatic tissue, to quantify the association between systemic measures of oxidative stress and antioxidant status, and to examine the relationship between retinoids and stellate cell activation. Methods Patients undergoing liver biopsy (n = 69) provided fasting blood, fresh tissue, urine and completed a diet history questionnaire. Serum and questionnaire data from healthy volunteers (n = 11), normal liver tissue from public repositories and patients without liver disease (n = 11) were also collected. Urinary isoprostanes, serum and tissue retinoid concentrations were obtained by UHPLC-MS-MS. Immunohistochemistry for αSMA was performed on FFPE sections and subsequently quantified via digital image analysis. Associations between urinary isoprostanes, αSMA levels, and retinoids were assessed using Spearman correlation coefficients and non-parametric tests were utilized to test differences among disease severity groups. Results There was a significant inverse association between serum retinol, lycopene, and RBP4 concentrations with fibrosis stage. Serum β-carotene and lycopene were strongly associated with their respective tissue concentrations. There was a weak downward trend of tissue retinyl palmitate with increasing fibrosis stage. Tissue retinyl palmitate was inversely and significantly correlated with hepatic αSMA expression, a marker for hepatic stellate cell activation (r = −0.31, P < 0.02). Urinary isoprostanes levels were inversely correlated with serum retinol, β-carotene, and RBP4. Conclusions A decrease in serum retinol, β-carotene, and RBP4 is associated with early stage HCV. Retinoid and carotenoid levels decline as disease progresses, and our data suggest that this decline occurs early in the disease process, even before fibrosis is apparent. Measures of oxidative stress are associated with fibrosis stage and concurrent antioxidant depletion. Vitamin A loss is accompanied by stellate cell activation in hepatic tissue.